Exploring the practices of secondary school teachers in preparing for classroom observation amidst the new normal of education - Caratiquit, Kevin; Pablo, Reynel (Journal of Social, Humanity, and Education, 2021)
Purpose: This study aimed to explore the practices of secondary public school teachers in preparing for classroom observation amidst the new normal of education. The emphasis of this study was drawn from the central question, "What are the practices of secondary public school teachers in preparing for classroom observation amidst the new normal of education?". Research Methodology: This study used a qualitative research design. It employed a phenomenology design to explore the practices of secondary public school teachers in preparing the new normal classroom observation. Results: Teachers believe that classroom observation is a measuring tool for achieving their professional goals or performance level. They also think that classroom observation can evaluate and assess the students' learning outcomes effectively and efficiently. Limitations: This study was limited to 22 secondary public school teachers in Cagayan, Philippines. Contribution: It can be helpful for teachers to improve their teaching techniques, strategies, methods, and instructional materials to be used amid this new normal of education.